PENGARUH DISIPLIN KERJA, PRODUKTIVITAS KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI KLINIK PRATAMA RAWAT INAP PKU MUHAMMADIYAH KETANGGUNGAN - Lusia Wulandari Soetejo; Siti . Juleha (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2021)
ABSTRACT This study takes the title Effect of Work Discipline, Work Productivity and Work Environment on Employee Performance at the PKU Muhammadiyah Keuntungan Inpatient Pratama Clinic.This study aims to:1) To determine the effect of work discipline, work productivity and work environment partially on employee performance at the PKU Muhammadiyah Keanggungan Inpatient Primary Clinic.2) To determine the effect of work discipline, work productivity and work environment simultaneously on employee performance.3) To find out the dominant influencing factors on employee performanceThe hypotheses in this study are:1) It is suspected that there is a partial effect of work discipline, work productivity and work environment on employee performance at the PKU Muhammadiyah Keanggungan Inpatient Pratama Clinic.2) It is suspected that there is an effect of Work Discipline, Work Productivity and work environment simultaneously on Employee Performance.3). It is suspected that work discipline has a dominant effect on employee performanceThis study uses a descriptive method, which is a method that seeks to describe a symptom, event, event that is happening now. Descriptive research focuses on actual problems as they were when the researcher took place:While the data collection method using questionnaire data.